Designing a Blockchain Technology-Based Treatment Cost Management Model in the Iranian Health System Using Content Analysis - Nahid Nargesi; Fatemeh Ahmadi; Sadegh Feizollahi; Rahmatollahr Mohammadipou (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  In recent decades, significant advances in information and communication technologies have provided new opportunities to improve the efficiency and effectiveness of health systems around the world. One of these technologies has great potential for transformation in health management: blockchain technology.  By providing a secure, transparent, and immutable platform for storing and transferring information, blockchain can help solve many of the challenges health systems face, including rising costs, insurance fraud, and problems in managing medical records. Therefore, the goal was to design a treatment cost management model based on blockchain technology in Iran's health system. Materials & Methods: The present research was conducted using a qualitative approach and thematic analysis method. Data was collected through semi-structured interviews. In 2024, the research community comprised professors and senior managers of the health system; based on the data saturation level, the snowball sampling method selected 15 individuals. The data were analyzed by thematic analysis and the Clark and Brown method using MAXQDA software. Results: 14 basic themes were identified in the form of 7 organizing themes and 1 overarching theme, which include economic factors, technological factors, regulatory factors, risk and legal factors, information system management, supply chain and logistics, and management and optimization. Conclusion: Blockchain technology can play an effective role in improving the quality of health services and reducing the financial burden on Iran's health system by improving the management of treatment costs. Investing in this technology and trying to solve the existing challenges can lead to a positive change in the country's health system.